Cerebral Venous Thrombosis: A Tunisian Monocenter Study on 160 Patients. (November 2017) - Sassi, Samia Ben; Touati, Nahla; Baccouche, Hela; Drissi, Cyrine; Romdhane, Neila Ben; Hentati, Fayçal
Objective: Data regarding cerebral venous thrombosis in North Africa are scarce. This study aims to identify the clinical features, risk factors, outcome, and prognosis of cerebral venous thrombosis in Tunisia. Methods: Data of 160 patients with radiologically confirmed cerebral venous thrombosis, hospitalized in Mongi Ben Hmida National Institute of Neurology (Tunis, Tunisia), were retrospectively collected and analyzed. Results: The mean age was 37.3 years with a female predominance (83.1%). The mode of onset was subacute in most cases (56.2%). Headache was the most common symptom (71.3%), and focal neurologic symptoms were the main clinical presentation (41.8%). The most common sites of thrombosis were the superior sagittal sinus (65%) and the lateral sinus (60.6%). More than 1 sinus was involved in 114 (71.2%) patients. Parenchymal lesions observed in 85 (53.1%) patients did not correlate with cerebral venous thrombosis extent. Major risk factors were obstetric causes (pregnancy and puerperium) found in 46 (38.6% of women aged <50 years) patients, followed by anemia (28.1%) and congenital or acquired thrombophilia (16.2%). Mortality rate was of 6.6%. Good outcome at 6 months (modified Rankin Scale ≤2) was observed in 105 (87.5%)of 120 patients available for follow-up. Predictors of poor outcome were altered consciousness and elevated plasma C-reactive protein levels. Conclusion: Clinical and radiologic presentation of cerebral venous thrombosis in Tunisia was quite similar to other parts of the world with, however, a particularly high frequency of obstetric causes. Plasma C-reactive protein level should be considered as a prognostic factor in CVT.